2018
DOI: 10.1080/19396368.2018.1516000
|View full text |Cite
|
Sign up to set email alerts
|

Artificial oocyte activation: physiological, pathophysiological and ethical aspects

Abstract: AOA: artificial oocyte activation; AOD: oocyte activation deficiency; Ca: Calcium; CAMKII: Ca/calmodulin-dependent protein kinase II; CICR: calcium-induced calcium-release; DAG: diacylglycerol; GM-CSF: granulocyte-macrophage colony-stimulating factor; ICSI: intra-cytoplasmic sperm injection; InsPR: inositol-trisphosphate receptor; IP: inositol 1,4,5-trisphosphate; IVF: in vitro fertilization; MAP: mitogen-activated protein; MII: metaphase II; NADP: nicotinic acid adenine dinucleotide phosphate; NO: nitric oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 103 publications
0
28
0
Order By: Relevance
“…Given the complexity of cellular mechanisms regulated by intra-cytoplasmic Ca 2+ levels and oscillations ( Alberio et al , 2000 ), Ca 2+ ionophores have raised concerns of molecular downstream consequences, issues with long-term gene expression and epigenetic alterations (i.e. DNA methylation), with possible implications affecting embryonic development post-implantation ( Ebner et al , 2012 ; Vanden Meerschaut et al , 2014b ; Santella and Dale, 2015 ; Capalbo et al , 2016 ; Nikiforaki et al , 2016 ; Anifandis et al , 2019 ). For example, protein synthesis and degradation changes in the first cell cycle may occur as a result of AOA, based on data with parthenogenetically activated mammalian oocytes ( Ebner and Montag, 2016 ).…”
Section: Efficacy and Safety Of Aoamentioning
confidence: 99%
“…Given the complexity of cellular mechanisms regulated by intra-cytoplasmic Ca 2+ levels and oscillations ( Alberio et al , 2000 ), Ca 2+ ionophores have raised concerns of molecular downstream consequences, issues with long-term gene expression and epigenetic alterations (i.e. DNA methylation), with possible implications affecting embryonic development post-implantation ( Ebner et al , 2012 ; Vanden Meerschaut et al , 2014b ; Santella and Dale, 2015 ; Capalbo et al , 2016 ; Nikiforaki et al , 2016 ; Anifandis et al , 2019 ). For example, protein synthesis and degradation changes in the first cell cycle may occur as a result of AOA, based on data with parthenogenetically activated mammalian oocytes ( Ebner and Montag, 2016 ).…”
Section: Efficacy and Safety Of Aoamentioning
confidence: 99%
“…Total fertilization failure (TFF) is a devastating outcome for couples undergoing IVF or ICSI. In ICSI cycles, TFF has been reported to occur in about 3% of cycles (44). Risk factors for TFF can include globoozospermia.…”
Section: Artificial Oocyte Activationmentioning
confidence: 99%
“…Different protocols exist but have been based on either chemical, mechanical or electrical stimulation of the oocyte following ICSI. These all ultimately lead to an influx of calcium into the ooplasm, theoretically mimicking the natural oocyte activation which occurs with normal fertilization (44).…”
Section: Artificial Oocyte Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, these studies have mainly focused on investigating the effectiveness of AOA in reproductive medicine, while few studies reported on the safety of this approach. In fact, ionophores, including A23187, exert many effects on cell homeostasis that might have a long-term effect on gene expression, some of which might be a threat and possible risk for epigenetics [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%